Chemistry An Introduction for Medical and Health Sciences - Jones, Alan (JOHN WILEY & SONS, 2005)
"Chemistry: An Introduction for Medical and Health Sciences provides students and practitioners with a clear, readable introduction to the chemical terms and concepts that are relevant to their study and practice. Assuming little prior knowledge of the subject, the book describes and explains the chemistry underlying many of the most commonly prescribed drugs and medicines. It also includes information on chemical aspects of digestion and nutrition, oxidation, radioactivity and an overview of how chemicals fight disease. The book contains a number of tests and questions, numerous good clear diagrams and boxes containing historical or topical vignettes." "Chemistry: An Introduction for Medical and Health Sciences will prove invaluable to students and practitioners in medicine, pharmacology, pharmacy and the biomedical and health sciences."--BOOK JACKET.